Investigation into the impacts of management’s non-implementation of audit recommendations to risks: case of national social security authority (NSSA) - Shumba, Vonai (Midlands State University, 2017)
The collapse of two local banks namely Capital and Interfin which lead to NSSA losing out significant volumes of money has probed a lot of questions to the entity’s major shareholders. The most frequently asked question was whether management is giving adequate attention to audit recommendations. This initiated the researcher to conduct a research to investigate the impacts of management’s non-implementation of audit recommendations to risks. The study prompted answers on sub-research questions of the research with the aim to highlight the reason and effects of non-implementation of recommendations and highlight ways to get action on recommendations. The study sample composed of directors, accounts clerks, accountants, bookkeepers and administration staffs. Research instruments considered for the purposes of this research are questionnaires which had 86% response rate and interviews which yielded 68% response rate. Data accumulated was analysed and presented through graphs, tables and pie charts and rational conclusions were drawn from this. Upon analysis of the accumulated data, the results of the study audit recommendations are not being given adequate attention and because of this the entity is at high overall business risk. The recommendations forwarded by the researcher are envisaged to lead to effective implementation of recommendations at National Social Security Authority.